Spread Risk Premia in Corporate Credit Default Swap Markets - Oliver Entrop; Richard Schiemert; Marco Wilkens (Credit and Capital Markets – Kredit und Kapital, 2014)
The spread risk premium component of credit default swap (CDS) spreads represents a compensation demanded by protection sellers for future changes in CDS spreads caused by unpredictable fluctuations in the reference entity"s risk-neutral default intensity. This paper defines and estimates a measure of the spread risk premium component in CDS spreads of a sample of European investment-grade firms by using a stochastic intensity credit model. Our results show that, on average, investors demand a positive premium for such mark-to-market risks. After controlling for CDS market conditions, like liquidity and supply/demand effects, a panel data analysis of the estimated spread risk premia reveals a positive impact of event risk captured by the overall stock market volatility and a negative impact of investors" appetite for exposure to credit markets as reflected by the overall CDS market. – – Marktrisikoprämien in Credit Default Swaps von Unternehmen Die Marktrisikoprämie im Credit Default Swap (CDS) Spread ist eine Kompensation für den Protection Seller für zukünftige Schwankungen des CDS-Spreads, die durch unvorhersehbare Fluktuationen der risikoneutralen Ausfallintensität des Referenzunternehmens verursacht werden. Dieser Aufsatz definiert und schätzt ein Maß für die Marktrisikoprämienkomponente im CDS-Spread unter Verwendung eines Kreditmodells mit stochastischer Ausfallintensität für eine Stichprobe europäischer Investment-Grade-Unternehmen. Unsere Ergebnisse zeigen, dass Protection Seller im Durchschnitt eine positive Prämie für die Übernahme von Marktrisiken verlangen. Eine Paneldatenanalyse der geschätzten Marktrisikoprämien findet zwei signifikante gemeinsame Faktoren, in der Form von Event Risk, erfasst durch die Aktienmarktvolatilität und der Nachfrage der Marktteilnehmer nach Kreditinvestments im Corporate Investment-Grade-Sektor, verkörpert durch den iTraxx Europe Index, selbst nach Bereinigung um Effekte durch Liquidität und Angebotsschocks im CDS-Markt.
Keywords: G12; G13; G15; 330; credit default swap; spread risk premium; mark-to-market risk premium; stochastic intensity model